Shape memory recovery in polylactic acid and thermoplastic polyurethane bi-material metamaterials fabricated by additive manufacturing under fatigue testing - Farzad Fereydoonpour; Shokouh Dezianian; Mohammad Azadi (Polymer Testing)
4D printing is defined as 3D printing plus the time. In this way, by applying a type of stimulus to the part fabricated by the 3D printing method and deformed, the sample returns to its original shape over time. This study advances the field of additive manufacturing by enhancing the design and functionality of shape memory polymers, enabling smarter, more adaptable materials for applications in aerospace. It can be mentioned as folding wings, solar sails, and actuator parts. In this research, the characteristics of the shape memory of the parts printed using fused deposition modeling (FDM) under fatigue loading were discussed. The printed parts comprised two types of polylactic acid polymer (PLA) and thermoplastic polyurethane (TPU). Three different percentages of the material composition were considered PLA, PLA/25TPU, and PLA/50TPU. Initially, rotary bending fatigue test was performed at a frequency of 100 Hz, but the samples delaminated. As a result, a vibration simulation was conducted using Abaqus software. The results showed that the natural frequency of the samples was very close to 100 Hz. To avoid resonance, the tests were conducted at a frequency of 20 Hz to obtain their lifetimes. Then, the shape memory recovery was implemented under fatigue (cyclic) loading by applying the time and temperature stimuli. A statistical sensitivity analysis was also done for the obtained results. Finally, the fracture surface of the specimens was evaluated by field-emission scanning electron microscopy (FE-SEM).The results of the rotary bending fatigue test showed that the fatigue lifetime decreased with the increase in the TPU percentage. In addition, the results of shape memory properties illustrated that with the addition of 25 % of TPU, the rate of deformation increased by 40 %, on average. Moreover, it was concluded that the temperature had about 64 % more influence than the time on shape memory properties. In addition, fatigue (cyclic) loading was 137 % more effective than static (monotonic) loading. The results of the statistical analysis also demonstrated that the shape memory properties increased with the enhancement of the TPU percentage. The images of the fracture surface showed the separation of layers and cavities, which were the factors of failures. Beach marks indicating the failure under fatigue loadings were also seen.